Determinants affecting the awareness of takaful products among students in UiTM KBM / Fatin Farhanah Md Noor and Sheik Ahmad Musa Sheik Mohd Fauzi - Md Noor, Fatin Farhanah; Sheik Mohd Fauzi, Sheik Ahmad Musa (Faculty of Business and Management, 2015)
The awareness of Takaful product has been shown to be very weak among of the user, so our research is focus on a future graduates whether they aware of Takaful product or not. The primary aim of this study is to explore the main factors that can contribute to the awareness of Takaful product. The data collected through questionnaire from 217 respondents was used to test the proposed hypothesis. The survey questions designed to determine three elements of awareness which include education factors, religion factors, and subjective norms factors. The result reveals the positive relationship of education, religion, and subjective norms with awareness of Takaful product. Factors and determinants that can help final year students aware in Takaful product have also been discussed. There are many other factors which may affect the level of awareness of Takaful but due to time constraint others are not taken for research. Moreover, the sample was also limited as the only focus was in final year UiTM KBM students based, excluding in other university. The accuracy of the results may be influenced by biases. The results of this study have clearly shown that the independent variables which are education, religion, and subjective norms have a direct and positive impact on the dependent variable that is awareness of Takaful product which means the enhancement of one independent variable causes the enhancement in the awareness which is the dependent variable.